Pengaruh Public Service Motivation terhadap Kepuasan Kerja melalui Keterlibatan Kerja Pegawai pada Dinas Perhubungan Kota Makassar - A Muh Ridha R; Andi Mustika Amin; Rezky Amalia Hamka; Uhud Darmawan Natsir; Rahmat Riwayat Abadi (MAMEN: Jurnal Manajemen, 2026)
This study aims to analyze the effect of Public Service Motivation on Job Satisfaction, both directly and indirectly through Work Engagement, among employees of the Department of Transportation of Makassar City. Understanding the relationship between these variables is essential to improve human resource management practices that foster high-quality public service and sustainable job satisfaction. This research employed a quantitative approach using a cross-sectional design. Data were collected through a structured questionnaire distributed to 95 employees of the Department of Transportation of Makassar City. The data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach to test both the direct and indirect effects among the studied variables. The results reveal that Public Service Motivation has a positive and significant effect on Job Satisfaction. Furthermore, Public Service Motivation also positively and significantly influences Work Engagement, and Work Engagement has a positive and significant impact on Job Satisfaction. The mediation analysis shows that Work Engagement partially mediates the relationship between Public Service Motivation and Job Satisfaction. This indicates that the motivation to serve the public not only directly affects job satisfaction but also indirectly through higher levels of work engagement.